Mariposas de la Reserva Biologica El Arenal, Matagalpa, Nicaragua - van den Berghe, E.=700 1 Maes, J.M.
(Es, En)
Ilus., 7 ref.
Keywords: LEPIDOPTERA; ESPECIES EN PELIGRO DE EXTINCION; BIODIVERSIDAD; HABITAT; RESERVAS NATURALES; NICARAGUA; MARIPOSAS; MATAGALPA; REVISTA NICARAGUENSE DE ENTOMOLOGIA